Factors affecting institutional delivery in Ethiopia: A multi-level analysis. (2021) - Gashaye, Aytenew; Kibret, Getiye Dejenu; Bazezew, Yibelu; Mengist, Belayneh
Abstract: Background: Childbirth is a complex process that requires the safest care to prevent maternal and neonatal complications. The proportion of births occurring at health institutions in Ethiopia is still below expected (26%), which significantly contribute to a large number of maternal deaths. Hence, identifying factors affecting institutional delivery is crucial. Objectives: The main objective of this study was to assess factors affecting institutional delivery among women who had a live birth in Ethiopia within five years preceding Ethiopian Demographic and Health Survey 2016. Method: The 2016 Ethiopian demographic and health survey data were used to identify factors associated with institutional delivery. As the data has nested structure, a multilevel logistic regression model was used for analysis by taking a nationally representative sample of 7193 women nested within 645 clusters. Result: A significant heterogeneity was observed between clusters for institutional delivery which explains about 53.5% of the total variation. Individual-level variables: higher-level women education (AOR = 5.74; 95% CI 2.7–9.73), parity 5, and more (AOR = 0.39; 95% CI 0.32–0.49) and the number of ANC visit four and greater visit (AOR = 6.74; 95% CI 4.11–11.04) were significantly associated with institutional delivery. Community-level variables, Community media exposure (AOR = 1.80; 95% CI 1.31–2.4) and community antenatal coverage (AOR = 1.97; 95% CI 1.18–3.30) had a significant effect on institutional delivery. Conclusion: The effort to promote institutional delivery should pay special attention to multiparous and less educated women.